Penerapan Metode SAW (Simple Additive Weighting) Dalam Pemilihan Saham Terbaik Pada Sektor Teknologi - Rosma Siregar; Kartika Sari; Siti Julianita Siregar (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Stocks are one of the many investments that are favored by all groups because they promise high returns. But in addition to promising high returns, stocks can also provide a high risk of loss, which makes ordinary people afraid to start investing in the stock market. To prevent losses in buying stocks is to choose stocks with good fundamentals. To support this, we need an analysis that can help make decisions in choosing the best stocks in the technology sector. The saw method analysis will be used in this study, where the saw method is able to select alternatives based on predetermined categories. This study will rank the best stocks based on company fundamentals, namely EPS, PER, PBV, ROE, DER and Dividend Yield. The results of this study are EDGE stocks as the best stocks in the technology sector with the highest value of 0.88. The purpose of this research is to help investors choose stocks before investing in technology companies.